Expression of human leucocyte antigen-G primarily targets affected skin of patients with psoriasis - Cardili, R. N.; Alves, T. G. [UNESP]; Freitas, J. C. O. C.; Soares, Christiane Pienna [UNESP]; Mendes-Junior, C. T.; Soares, E. G.; Donadi, E. A.; Silva-Souza, C. (Wiley-Blackwell, 2010)
P>BackgroundThe nonclassical human leucocyte antigen (HLA)-G molecule has been well recognized as a tolerogenic molecule and few studies have evaluated the role of the molecule in inflammatory cutaneous autoimmune diseases.ObjectivesTo evaluate the expression of HLA-G in skin specimens of patients with psoriasis and to analyse its correlation with epidemiological and clinical variables.MethodsThirty untreated patients with psoriasis and 32 healthy individuals were enrolled. Immunohistochemistry was applied to identify HLA-G expression in formalin-fixed paraffin-embedded cutaneous skin biopsies.ResultsSoluble and membrane-bound HLA-G expression was detected in 30 (90%) of the skin specimens from patients presenting clinical and histopathological features of psoriasis. Although infiltrating lymphomononuclear cells of the dermis exhibited HLA-G expression, the epidermis was primarily targeted. HLA-G expression was also observed in 27% (three of 11) of the specimens that exhibited no clinical and histopathological features of psoriasis (nonaffected areas). In contrast, skin specimens obtained from healthy individuals exhibited no HLA-G expression (P < 0 center dot 0001). The intensity of HLA-G expression was not associated with type I/II psoriasis, Psoriasis Area and Severity Index score or clinical forms.ConclusionsAs the HLA-G molecule was consistently expressed in affected and, to a lesser extent, in nonaffected areas of untreated patients with psoriasis, irrespective of the severity of the clinical variants, one may hypothesize that the presence of HLA-G may be responsible, at least in part, for the regulation of autoimmune effector cells.
Keywords: autoimmunity; HLA-G; inflammation; psoriasis